1984
DOI: 10.1523/jneurosci.04-03-00832.1984
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptide modulation of photosensitivity. I. Presence, distribution, and characterization of a substance P-like peptide in the lateral eye of Limulus

Abstract: The lateral eye of Limulus is innervated by an efferent system of fibers containing a substance P-like peptide. They were detected and their distribution was studied using indirect immunocytochemical techniques and monoclonal and serum antibodies. These thin, efferent fibers travel up the optic nerve, cross the lateral plexus, and branch out profusely when reaching the ommatidial layer. Innervation is extended to more than one component of the ommatidia, including the pigment, retinular, and eccentric cells. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1985
1985
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Furthermore, as is described later in this review, application of octopamine to the eyes mimics many of the biochemical, electrophysiological, and anatomical effects of endogenous circadian efferent nerve activity (See Table 1). A second type of efferent projection to the lateral eyes has been described that consists of substance P (SP)-and FMRFamide-immunoreactive axons (Chamberlain and Engbretson, 1982;Mancillas and Brown, 1984;Mancillas and Selverston, 1985). But these SP/FMRFamide efferents are part of a general cuticular innervation and entirely separate from the octopaminergic system.…”
Section: Octopamine-containing Retinal Efferent Neurons Mediate Circamentioning
confidence: 99%
“…Furthermore, as is described later in this review, application of octopamine to the eyes mimics many of the biochemical, electrophysiological, and anatomical effects of endogenous circadian efferent nerve activity (See Table 1). A second type of efferent projection to the lateral eyes has been described that consists of substance P (SP)-and FMRFamide-immunoreactive axons (Chamberlain and Engbretson, 1982;Mancillas and Brown, 1984;Mancillas and Selverston, 1985). But these SP/FMRFamide efferents are part of a general cuticular innervation and entirely separate from the octopaminergic system.…”
Section: Octopamine-containing Retinal Efferent Neurons Mediate Circamentioning
confidence: 99%
“…The antisubstance P antiserum (TG2-4), a gift from M.R. Brown (University of California, San Diego, CA), has been characterized by Mancillas and Brown (1984). Its specificity in locust brain tissue has been shown by Wü rden and .…”
Section: Antiseramentioning
confidence: 99%
“…4 showed that partial bisection of the brain desynchronized the burst activity from efferent fibers from the two halves of the brain. Mancillas and Brown (1984) concluded that efferent fibers from the circadian clock exit the brain from dorsal nerves 3 and 4 and terminate in the lateral eye. Anatomical studies show that the efferent cell bodies are located in the chelicera ganglion (Caiman & Battelle, 1991;Lee & Wyse, 1991) and send nerve fibers out ipsilateral optic nerve trunks as well as across the midline to the contralateral side.…”
Section: One Circadian Oscillator or Two?mentioning
confidence: 99%